Teaching history with the video game Assassin's Creed: effective teaching practices and reported learning - THIERRY KARSENTI; SIMON PARENT (Metaichmio Publications, 2020)
This article presents the main results of an exploratory study on the educational impacts of the video game Assassin's Creed during a history class in a high school located in Quebec, Canada. The main objectives of the research were to describe how the game was used in school, the benefits of using it in an educational context and identify the challenges of such a use of the game.